Analysis of the Implementation of Good Governance Principles in Public Services in Pantai Lango Village, Penajam District, Penajam Paser Utara Regency - Alamsah, Andi Nour; Samad, Abdul; Suyuthi, Nurmadhani Fitri (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
This study aims to analyze the extent to which the principles of good governance are implemented at Kelurahan Pantai Lango in the context of public service. Additionally, it seeks to assess how the application of these principles impacts public services in Kelurahan Pantai Lango. The research employs a qualitative approach. Data were collected through in-depth interviews with various informants, including local officials and community members, to gather qualitative insights into the practices and impacts of good governance in Kelurahan Pantai Lango. The collected data were then analyzed using interactive model analysis techniques. The findings reveal that Kelurahan Pantai Lango has successfully implemented the principles of good governance in public service. These principles participation, transparency, justice, accountability, and efficiency have been applied in various ways aimed at improving public service. The impact of applying these principles on public service in Kelurahan Pantai Lango is positive. Community members reported improvements in information access, participation in decision-making, and service speed.